Biotechnological Applications of Microbes - Varma, Ajit;Ed. Podila, Gopi K;Ed (Microbiology Series, 2., 2005)
Understanding Microbes is vital to understand the past and the future of mankind and our planet. This book focuses on diverse areas of microbial research and provides information on the microbial world - biochemistry of the molecules, their functions, syntheses, and regulation activity; microbial genetics, immunology, and biotechnology.